STUDY OF URBAN DEVELOPMENT BY APPLYING GEOGRAPHIC INFORMATION SYSTEMS AND REMOTE SENSING TECHNIQUES (FALLUJA CITY AS A CASE STUDY) - N. Sayle, Khamis (Anbar Journal of Engineering Sciences, 2008)
The progress in technological earth observation field , using of satellite data and the development of computer software, lead to reduce effort and time to control the change in land uses especially after the increases in both accuracy and resolution of image data. This paper studies the urban development of falluja city since its construction (depending on the fact of land uses) and future directions for the development of the city. The above two trends are very important in supporting decisions of governorates, municipalities and government departments in the land uses management and control of building by using a new technique which treated with data and uses maps. The present study concluded that the use of remote sensing, geographic information system and mathematical models are very important to prepare master plan of cities with high efficiency.